Larix laricina bark, a traditional medicine used by the Cree of Eeyou Istchee: Antioxidant constituents and in vitro permeability across Caco-2 cell monolayers. (24th December 2016) - Yong, Yi; Saleem, Ammar; Guerrero-Analco, José A.; Haddad, Pierre S.; Cuerrier, Alain; Arnason, John T.; Harris, Cory S.; Johns, Tim
Abstract: Ethnopharmacological relevance: Larix laricina, a native tree of North America, is a highly respected medicinal plant used for generations by Indigenous Peoples across its range, including the Cree of northern Québec who use the bark to treat symptoms of diabetes. This study investigates the antioxidant capacity and bioavailability of active constituents identified in L. laricina bark extracts. Materials and methods: (1) Oxygen radical absorbance capacity (ORAC) assay was employed to test antioxidant capacity of organic extracts (80% ethanol) from bark of L. laricina as well as fractions, isolated compounds, and media samples collected during permeability assays. (2) Caco-2 cell monolayer cultures were used to determine the permeability of identified antioxidants, which were quantified in basolateral media samples using liquid chromatography – tandem mass spectrometry (HPLC-ESI-MS/MS). Results: Crude ethanolic extract possessed strong antioxidant potential in vitro (7.1±0.3 Trolox equivalents (TE) μM/mg). Among the 16 L. laricina fractions obtained by chromatographic separation, fraction 10 (F10) showed the highest antioxidant capacity (21.8±1.7 µm TE/mg). Among other identified antioxidants, the stilbene rhaponticin (isolated from F10) was the most potent (24.6±1.1 µm TE/mg). Caco-2 transport studies revealed that none of the identified compounds were detectable in basolateral samples after 2-h treatment with crude extract. In monolayers treated with F10 (60% rhaponticin), small quantities of rhaponticin were increasingly detected over time in basolateral samples with an apparent permeability coefficient (Papp ) of 1.86×10 −8 cm/s (0–60 min). To model potential effects on blood redox status, we evaluated the antioxidant capacity of collected basolateral samples and observed enhanced activity over time after exposure to both extract and F10 (75 μg/mL) relative to control. Conclusions: By profiling the antioxidant constituents of L. laricina bark, we identified rhaponticin as the most potent oxygen radical scavenger and observed low permeability in Caco-2 cell monolayers but an increase in basolateral antioxidant capacity. Graphical abstract: